CHANGE IN LAND USE/LAND COVER USING REMOTELY SENSED IMAGES IN KAFANCHAN AREA OF KADUNA STATE, NIGERIA - Mande, Hosea Kato; Olaniyi, Akeem O.; Richard, Mercy; Sule, Bulus; Abasha, Deborah (FUDMA JOURNAL OF SCIENCES, 2023)
Vegetation cover in Kafanchan has been on the decrease which has suffered more and undue depletion and degradation. This research assessed the change of land use/land cover for the span of 45 years (1988-2023). This study made use of LANDSAT 2, 4, 8 and 8 images of the year 1988, 1998, 2016 and 2023 accordingly. The images were processed using Arcmap 10.3. For the secondary data collection, the area was demarcated into bare land, water bodies, vegetation and built-up areas. The results shows that there has been an increase of built-up areas from 28.19% of the study area in 1988 to 44.73% in 1998 and 45.98% in 2023. Vegetation land use has also shown a decrease from 49.75% in 1988 to 30.54% in 2023. Water bodies decreased from 12.3% in 1988 to 10.92% in 2023. Vegetated land was the most dominant land cover class in the study area but decreased to 28.84% in 1998, and increase from 28.84% in 1998 to 30.54% in 2023 this is supported by the continuous decline of high-end Normalized Difference vegetation index (NDVI) values from 1988 (0.536), 1998 (0.411), 2016 (0.380) and 2023 (0.280) implying that vegetation cover in Kafanchan is steadily being depleted. The applications of RS and GIS will promote better understanding in the monitoring of land use-land cover interactions to aid planning, management and enterprise.